Komunikasi Bersifat Nonsekuensial - Effendy, Erwan; Siregar, Nurhalija Patonah; Andini, Andini; Purnama, Rahma Aulia Sukma (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
The purpose of this study is to find out about non-sequential communication. Which in this study used qualitative research methods, namely the method of literature review and literature review. As social beings, humans always want to be in touch with other humans. This curiosity forces humans to communicate. In a Non-sequential Communication process, communication may occur in a random order; not linear, circular, or even helical. In non-sequential communication, the communicator can become a communicant, and vice versa, the communicant can turn into a communicator. For example, communication between two people actually simultaneously involves communicating with oneself (thinking) to respond to the other party. Keywords: Communication, Interaction, and Nonsequential